A privacy and delegation-enhanced user authentication protocol for Portable Communication Systems. (1st September 2010) - Wang, Ren-Chiun; Juang, Wen-Shenq; Lei, Chin-Laung
Recently, Lee et al. proposed a security enhanced delegation-based authentication protocol for Portable Communication Systems (PCSs). The major merits include: 1) the privacy protection of Mobile User (MS); 2) MS can construct a digital signature to prove the requests; 3) the satisfaction of some security properties; 4) the mutual authentication between MS and the Visited Location Register (VLR); 5) low computation and communication cost of MS. We then show that the privacy of MS is not kept and the overcharge problem exists in Lee et al.'s protocol and propose a method to enhance the delegation and security level and to keep the same efficiency.